Intellectual property : patents, copyright, trade marks and allied rights. - Cornish, W. R. (William Rodolph), 1937-; Llewelyn, David; Aplin, Tanya Frances, 1972-; dawsonera (London : Sweet & Maxwell, 2013)
Cornish, Llewelyn & Aplin's Intellectual Property has developed a reputation amongst IP academics and practitioners as an accurate, straight forward (and straight to the point) in depth guide to every aspect of Intellectual Property law. For the student the thoughtful analysis of every area guides the reader whilst prompting questions and issues for the reader to develop further. As a "flip and find" practitioner reference work IP professionals will rarely allow their copy to gather dust. --
PART I Common Ground -- 1. Starting Points -- 2. The Enforcement Of Rights -- PART II PATENTS -- 3. Growth And Purpose Of Patents -- 4. The Patent: Grant And Content -- 5. Validity -- 6. Scope Of Monopoly -- 7. Property Rights And Exploitation -- PART III Confidence and Personal Privacy -- 8. Confidential Information -- 9 Personal Privacy -- PART IV Copyright and Designs -- 10. Range And Aims Of Copyright -- 11. Subsistence Of Copyright -- 12. Infringement Of Copyright And Moral Rights -- 13. Property Rights And Exploitation -- 14. Copyright: Particular Cases -- 15. Industrial Design -- PART V Trade Marks and Names -- 16. Competitor And Consumer -- 17. Common Law Liability -- 18. Registered Trade Marks -- PART VI The European Dimension and New Technologies -- 19. Intellectual Property In The European Union -- 20. Digital Technology: Computers And The Internet -- 21. Intellectual Property in Biotechnology.
Restrictions on access to electronic version: access available to SOAS staff and students only, using SOAS id and password.
Previous edition: 2010.
Includes bibliographical references and index.
Keywords: Intellectual property -- Great Britain; Intellectual property; Great Britain